(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the multifaceted importance of corpus-based linguistics in English language education, focusing on its crucial function in fostering authentic language use, facilitating research-based teaching methodologies, and increasing students’ linguistic competence across registers and contexts. Through an exhaustive review of current literature and empirical evidence, this paper highlights the transformative influence of corpus-based approaches on language learning, vocabulary development, error analysis, and research skill advancement. This study explores the integration of corpus-based linguistics into secondary school English language teaching, focusing on the use of Sketch Engine for Language Learning (SKELL) as a tool for improving vocabulary acquisition, writing skills, and overall language proficiency. The study examines how the corpus-based approach, grounded in real-world language data, enhances learner engagement, promotes autonomous learning, and supports the development of critical thinking and creativity. The research was conducted with a group of secondary school students, revealing that SKELL’s user-friendly interface, authentic language examples, and multilingual support provide significant advantages in language learning. The results suggest that incorporating SKELL into English language teaching can effectively address common challenges faced by adolescent learners, such as vocabulary retention and usage, while fostering a deeper understanding of language through context.